UTILIZATION OF DIGITAL MARKETING IN SUSTAINABLE TOURISM DEVELOPMENT IN PEMATANG JOHAR - Muammar Rinaldi; Ihdina Gustina; Putri Wahyuni; Dedy Lazuardy (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This community service activity aims to improve the digital capabilities of MSMEs and rice field tourism managers in Pematang Johar Village, Deli Serdang Regency, through the implementation of digital marketing to support sustainable tourism development. This village has significant potential in the agrotourism and local product sectors, but has not been fully optimized through technology-based promotional strategies. The activity was implemented using a participatory and educational approach, including preparation, training, mentoring, and evaluation. A total of 30 participants consisting of MSMEs and village tourism managers participated in training on creating digital business accounts, designing promotional content, and implementing marketing strategies through social media and marketplaces. Evaluation was carried out through pre- and post-tests to measure participants' understanding, as well as field observations of the practical application of the training outcomes. The results showed significant improvement, with 87% of participants able to operate digital promotional media independently. The implementation of digital marketing strategies had a positive impact on increasing local product sales by 40% and tourist visits by 25%. This activity demonstrated that digitalization of tourism promotion and MSMEs can strengthen the synergy between sustainable tourism and community economic empowerment, as well as create a technology-based, inclusive and sustainable tourism village development model.